Flow characterization of gas-solid mixture in fluidized bed combustion - Rosyida Permatasari, 1966-, author; Mohammad Nazri Mohd. Jaafar, 1963-, author; Tholudin Mat Lazim, author; Mohammad Sayuthy Samsudin, author; Engineering Conference on energy and Envronment (1st : 2007 : Serawak) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL